Perancangan Controller - Djunaidi Santoso (Bina Nusantara University, 2010)
In making controller, there must be knowledge about component controlling functions that used for controller designing. In the control unit, it needs simple method as micro programming. This micro programming is to create a micro program in binary numbering that used for controlling pin’s component controller and outside the controller. Controller design in general needs several prerequisites, which are digital system and controller and assembly language.